2015
DOI: 10.1016/j.ejmech.2015.04.056
|View full text |Cite
|
Sign up to set email alerts
|

Exploring quercetin and luteolin derivatives as antiangiogenic agents

Abstract: The formation of new blood vessels from the pre-existing vasculature (angiogenesis) is a crucial stage in cancer progression and, indeed, angiogenesis inhibitors are now used as anticancer agents, clinically. Here we have explored the potential of flavonoid derivatives as antiangiogenic agents. Specifically, we have synthesised methoxy and 4-thio derivatives of the natural flavones quercetin and luteolin, two of which (4-thio quercetin and 4-thio luteolin) had never been previously reported. Seven of these com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 46 publications
3
35
1
1
Order By: Relevance
“…This concentration had no effects on the tube formation of vascular endothelial cells, another cell migratory process [63]. In fact, the migration of blood endothelial cells during angiogenesis depends on VEGF/VEGFR2 instead of MMP2/9, and quercetin interferes with VEGFR2 expression [64,65]. However, in lymph endothelial cells, the VEGF/VEGFR2 signaling is not observed during intravasation of MCF-7 cells [13].…”
Section: Discussionmentioning
confidence: 97%
“…This concentration had no effects on the tube formation of vascular endothelial cells, another cell migratory process [63]. In fact, the migration of blood endothelial cells during angiogenesis depends on VEGF/VEGFR2 instead of MMP2/9, and quercetin interferes with VEGFR2 expression [64,65]. However, in lymph endothelial cells, the VEGF/VEGFR2 signaling is not observed during intravasation of MCF-7 cells [13].…”
Section: Discussionmentioning
confidence: 97%
“…In previous studies, some thioxoflavonones showed no or less antiproliferative activity in nine human cancer cell lines (A375, HCT‐15, BxPC3, MCF‐7, MCF‐7‐ADR, A431, A431/Pt, OV2008, and C13*) than correspondent flavones . However, we could find that a translation of carbonyl (CO) group into thiocarbonyl (CS) group could significantly improve their antiproliferative activities of the parent flavones on three human cancer cell lines (HeLa, HCC1954, and SK‐OV‐3).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the key role of sulfur‐containing small molecules and enzymes in a wide range of essential biological functions led researchers to focus intensely on developing new thio‐compounds to treat or prevent diseases, thioxoflavones have been reported to show special anticancer, antimicrobial, and neuroprotective activities .…”
Section: Introductionmentioning
confidence: 99%
“…The pentahydroxy avone (quercetin) derivatives (5c-f) were obtained starting from pentahydroxy avone (purchased) according to Scheme 3 27,28 in 36% overall yield and with 99% purity by HPLC. This represents an improvement on the recently reported synthesis of 5f, both in terms of overall yield and purity 29 (22% overall yield and 95% purity).…”
Section: Design and Synthesismentioning
confidence: 99%